Fault zone architecture of a large plate-bounding strike-slip fault: a case study from the Alpine Fault, New Zealand - B. Schuck; B. Schuck; A. M. Schleicher; C. Janssen; V. G. Toy; V. G. Toy; G. Dresen; G. Dresen (Solid Earth, 2020)
New Zealand's Alpine Fault is a large, plate-bounding strike-slip fault, which ruptures in large (Mw>8) earthquakes. We conducted field and laboratory analyses of fault rocks to assess its fault zone architecture. Results reveal that the Alpine Fault Zone has a complex geometry, comprising an anastomosing network of multiple slip planes that have accommodated different amounts of displacement. This contrasts with the previous perception of the Alpine Fault Zone, which assumes a single principal slip zone accommodated all displacement. This interpretation is supported by results of drilling projects and geophysical investigations. Furthermore, observations presented here show that the young, largely unconsolidated sediments that constitute the footwall at shallow depths have a significant influence on fault gouge rheological properties and structure.